Kobatama Sebagai Salah Satu Pionir Industri Olahraga Di Indonesia - Tsai’in Raihan Firmansyah; Anwari, Ikhsan (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Basketball in Indonesia is not only present as a popular sport but has also developed into an industry that sustains various stakeholders, ranging from players, coaches, and club managers to supporting communities. However, previous studies have tended to focus more on the technical aspects of the game or athletes’ achievements, while the perspective of basketball as an industry has rarely been explored. This research focuses on Kobatama as the national basketball league that played an important role in the development of the sports industry in Indonesia. The timeframe of 1994–1998 was chosen, as this period marked both significant progress in Kobatama’s development as an industry and the serious challenges posed by the national monetary crisis. Employing the historical method—comprising heuristics, source criticism, interpretation, and historiography—this study finds that Kobatama was not merely a competitive arena, but also fostered the formation of a sports industry ecosystem through funding mechanisms, player professionalization, and the strengthening of fan bases. The contribution of this study lies in expanding the historiography of Indonesian sports beyond technical aspects toward an understanding of basketball as a socio-economic phenomenon, while also providing an important foundation for the future development of the sports industry.